Anatomical and clinical factors favoring the performance of saphenous ablation and microphlebectomy or sclerotherapy as a single-stage procedure. (October 2015) - Kokkosis, AA; Schanzer, H
Objective: To identify the anatomical and clinical parameters that predict lack of regression of superficial varicosities after ablation of the great saphenous vein. Methods: Symptomatic patients treated with endovenous ablation from August 2006 to July 2013, by a single surgeon, were included. Recorded parameters included age, sex, size, and extent of varicosities (class I–IV) (patient standing), and diameter and length (patient supine) of treated great saphenous vein. Varicose vein classification was defined as: class I ≤6 mm and localized to thigh or leg, class II ≤6 mm and present in the thigh and leg (extensive), class III >6 mm and localized to the thigh or leg, and class IV >6 mm and extensive. "Excellent" results were defined as complete resolution of varicosities, "good" results as incomplete resolution, and "poor" results as no improvement. Results: A total of 267 patients and 302 consecutive limbs were included in the study. There were 175 females (65.5%), and the mean age was 54 years old (22–92). The CEAP classification was as follows: C2 (81.5%), C3 (6.3%), C4 (7.9%), C5 (2.0%), and C6 (2.3%). Great saphenous vein diameters was significantly larger in patients with C3–C6 (proximal 0.84 ± 0.25 versus 0.65 ± 0.21, p = < 0.0001, distal 0.58 ± 0.18 versus 0.44 ± 0.13, p < 0.0001) or class III–IV varicose veins (proximal 0.85 ± 0.25 versus 0.75 ± 0.27, p = 0.012, distal 0.62 ± 0.62 versus 0.50 ± 0.17, p < 0.0001). Class III–IV limbs had a "good/poor" result 69.8% of the time, as compared to 51.9% of the limbs class I–II varicose veins (p = 0.002). Conclusions: Advanced chronic venous disease (C3–C6) patients have larger diameter great saphenous veins, reflecting the progressive nature of the disease. Patients with more severe varicosities regardless of CEAP class were more likely to require a secondary procedure. The severity of the varicosities may not correlate with the degree of venous disease, but it is an indication of which patients should undergo secondary procedures, possibly with a one-stage approach.